Current management of myocardial infarction - Jankowski, Piotr; Brzozowska-Kiszka, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2009)
All patients with ST elevation acute coronary syndromes (ACS) should undergo reperfusion therapy as quickly as possible. As the results of primary angioplasty are significantly better when compared with thrombolysis the invasive approach should be preferred in almost all cases and, if possible, all patients should be immediately transferred to centres with 24-hour access to a catheterization laboratory. Transportation to a hospital without such capability should be considered as a waste of time. It should be underlined that such practice can lead to worse prognosis of myocardial infarction patients. Pharmacological treatment should be started as early as possible in the pre-hospital phase (antiplatelets, morphine, nitrate if required) followed by prescription of b-blocker, ACE inhibitor and statin in most cases. The long-term prognosis depends considerably on appropriate control of risk factors. The management of acute coronary syndromes without ST elevation has become more and more similar to the management of ST-elevation ACS recently. Currently, the major differences are: no indications for thrombolytic treatment and acceptable longer time to coronary angiography in most cases of ACS without ST elevation.